2011
DOI: 10.2196/jmir.1519
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Acceptability and Usability of an Interactive Serious Game in Aiding Treatment Decisions for Patients with Localized Prostate Cancer

Abstract: BackgroundMen diagnosed with localized prostate cancer face a potentially life-altering treatment decision that can be overwhelming. Enhancing patient knowledge through education can significantly reduce feelings of uncertainty while simultaneously increasing confidence in decision making. Serious games have been shown in other populations to increase health knowledge and assist with the health decision-making process. We developed an interactive serious game, Time After Time, which translates evidence-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 51 publications
(63 reference statements)
3
63
1
1
Order By: Relevance
“…The majority of studies did not integrate the oldest old as a meaningful proportion of the sample, despite the increasing [10][11][12]14,17,[21][22][23][24][25][28][29][30][31][32][33][34][35][36][37][38][39][40]42,[44][45][46][47][48][49][50][51][52][53][54] To clarify sample proportions and enable our analysis, two authors contacted the respective authors seeking further clarification of the actual number of participants q85 years of age when necessary. Consistent with previous reviews, 2-5 this study highlights a substantial gap in the knowledge base and encourage further exploration into digital gaming use in those 85 years of age and greater.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of studies did not integrate the oldest old as a meaningful proportion of the sample, despite the increasing [10][11][12]14,17,[21][22][23][24][25][28][29][30][31][32][33][34][35][36][37][38][39][40]42,[44][45][46][47][48][49][50][51][52][53][54] To clarify sample proportions and enable our analysis, two authors contacted the respective authors seeking further clarification of the actual number of participants q85 years of age when necessary. Consistent with previous reviews, 2-5 this study highlights a substantial gap in the knowledge base and encourage further exploration into digital gaming use in those 85 years of age and greater.…”
Section: Discussionmentioning
confidence: 99%
“…Although an age range was described, it is possible there is a publication bias or a failure of studies to report actual age range. Some studies 24,25,35,39,40,46 only reported the age range with no mean or standard deviation; conversely, five studies 10,27,30,32,33 reported the mean age but no age range or standard deviation. Albeit the authors were able to substantiate some aspect of the participants' ages, the authors believe future studies should use clear measures to depict the exact number of participants q85 years of age and aim to have a proportionate representation of older adults in studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El uso de Internet, por ejemplo, ha posibilitado que los programas terapéuticos puedan llegar a aquellos pacientes que les resulta difícil el traslado hasta sus centros de salud, ya sea por la enfermedad, la ubicación geográfica o cualquier otra razón (1)(2)(3) . Otro ejemplo lo constituyen los denominados "juegos serios" (serious games), juegos digitales creados con propósitos que van más allá del entretenimiento, que facilitan la entrega de información médica y de herramientas de apoyo para la toma decisiones y la implicación en conductas saludables (4)(5)(6) . En los últimos años se está también comenzando a indagar acerca de la viabilidad y los beneficios asociados a la evaluación electró-nica en este tipo de pacientes, fundamentalmente mediante ordenador (7)(8)(9) , y se han generado aplicaciones móviles dirigidas a monitorizar y ayudar al manejo de la sintomatología desde casa (10)(11) , además de servir de apoyo a programas online, gracias a la posibilidad que ofrecen para registrar síntomas, recibir mensajes y acceder a módulos del programa (12) .…”
Section: Introductionunclassified